HINDU MATHEMATICS IN MODERN ARITHMETIC: ASSESSING STUDENT AWARENESS AND UNDERSTANDING - Nabil, Muhammad; Harisman, Yulyanti (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Hindu mathematics has made foundational contributions to the development of modern arithmetic, particularly through the introduction of the decimal number system and the concept of zero. Despite its historical significance, this study found that students' awareness and understanding of Hindu mathematics remain limited. This research investigates the role of Hindu mathematics in shaping modern arithmetic and examines students’ knowledge of these contributions. The study employed a qualitative approach, combining a literature review to trace historical developments with student interviews to assess their conceptual understanding. Findings indicate a substantial gap in students’ historical awareness, with most attributing the origins of modern arithmetic solely to Western and Arabic traditions. This gap is attributed to curriculum content that underrepresents non-Western mathematical heritage and a lack of accessible instructional resources. The study underscores the need to integrate Hindu mathematical contributions more explicitly into mathematics education to foster a more comprehensive and culturally inclusive understanding of the discipline’s history.